Highly Selective Optical Detection of Fe3+ Ions in Aqueous Solution Using Label‐Free Silicon Nanocrystals. (27th February 2019) - Linehan, Keith; Carolan, Darragh; Doyle, Hugh
Abstract: High brightness amine‐terminated silicon nanocrystals (Si NCs) have been utilized in a simple and rapid assay for the highly selective and sensitive detection of Fe 3+ via quenching of their strong blue luminescence, without the need for analyte‐specific labeling groups. Sensitive detection of Fe 3+ is successfully demonstrated, with a linear relationship observed between luminescence quenching and Fe 3+ concentration from 5 × 10 −6 to 900 × 10 −6 m and a limit of detection of 1.3 × 10 −6 m . The Si NCs show excellent selectivity toward Fe 3+ ions, with no quenching of the luminescence signal induced by the presence of Fe 2+ ions, allowing for solution phase discrimination between the ionic species in different charge states. Abstract : Luminescence quenching in Si nanocrystals (NCs) has been used for the selective detection of ferric (Fe 3+ ) ions from 5 × 10 −6 to 900 × 10 −6 m with a limit of detection of 1.3 × 10 −6 m . The Si NCs are impervious to interference from other transition metal ions and can discriminate between Fe 3+ and Fe 2+ ions at all concentrations.